Expression, regulation and activity of a B2-type cyclin in mitotic and endoreduplicating maize endosperm - Sabelli, Paolo A.; Dante, Ricardo A.; Nguyen, Hong N.; Gordon-Kamm, William J.; Larkins, Brian A. (Frontiers in Plant Science, 2014)
Cyclin-dependent kinases, the master regulators of the eukaryotic cell cycle, are complexes comprised of a catalytic serine/threonine protein kinase and an essential regulatory cyclin. The maize genome encodes over 50 cyclins grouped in different types, but they have been little investigated. We characterized a type B2 cyclin (CYCB2;2) during maize endosperm development, which comprises a cell proliferation phase based on the standard mitotic cell cycle, followed by an endoreduplication phase in which DNA replication is reiterated in the absence of mitosis or cytokinesis. CYCB2;2 RNA was present throughout the period of endosperm development studied, but its level declined as the endosperm transitioned from a mitotic to an endoreduplication cell cycle. However, the level of CYCB2;2 protein remained relatively constant during both stages of endosperm development. CYCB2;2 was recalcitrant to degradation by the 26S proteasome in endoreduplicating endosperm extracts, which could explain its sustained accumulation during endosperm development. In addition, although CYCB2;2 was generally localized to the nucleus of endosperm cells, a lower molecular weight form of the protein accumulated specifically in the cytosol of endoreduplicating endosperm cells. In dividing cells, CYCB2;2 appeared to be localized to the phragmoplast and may be involved in cytokinesis and cell wall formation. Kinase activity was associated with CYCB2;2 in mitotic endosperm, but was absent or greatly reduced in immature ear and endoreduplicating endosperm. CYCB2;2-associated kinase phosphorylated maize E2F1 and the “pocket” domains of RBR1 and RBR3. CYCB2;2 interacted with both maize CDKA;1 and CDKA;3 in insect cells. These results suggest CYCB2;2 functions primarily during the mitotic cell cycle, and they are discussed in the context of the roles of cyclins, CDKs and proteasome activity in the regulation of the cell cycle during endosperm development.